Evidencing the outsourcing of social care provision in England - Bach-Mortensen, A; Goodair, B; Degli Esposti, M; Corlet Walker, C; Barlow, J (Nuffield Foundation, 2024)
This project created a comprehensive, longitudinal data resource on outsourcing trends and their associations with key outcomes in adult and children's social care provision across England.